Using the Science-Policy Interface Platform of the UNCCD to translate current WLE science into policy options, to demand driven outputs and accelerate adoption of policy recommendation - CGIAR Research Program on Water, Land and Ecosystems (2019)
Distributed to the COP to the 197 UNCCD member countries. The 122 countries which have agreed to make the Sustainable Development Goal of achieving land degradation neutrality a national target in particular could implement the recommendations.